Nutritional Role In Age Related Macular Degeneration (International Journal of Food and Nutritional Sciences, 2023)
Age related macular degeneration (ARMD) is the leading cause of significant visual acuity loss in people over age of 50 in developed countries, it is the common aging eye disease that cause visual impairment in aging population, and it's characterized by the loss in the center field of vision and leaky blood vessels grow under the retina. Globally, ARMD ranks third as a cause of blindness after cataract and glaucoma in general, advanced AMD is a rare disease, before the age of 55, and more common among the persons of 75 years and older.